In-situ synthesis of molecular magnetorefrigerant materials - Liu, Sui-Jun; Han, Song-De; Zhao, Jiong-Peng; Xu, Jialiang; Bu, Xian-He (Coordination chemistry reviews, 2019)
[Display omitted] This review summarized recent research progresses on the in-situ synthesis of molecular magnetorefrigerant materials derived from organic ligands, metal ions and templates generated in-situ. •In-situ synthetic strategy for the construction of molecular magnetorefrigerant materials has been reviewed.•Molecular magnetorefrigerant materials with ligands, metal ions and templates formed in-situ have been illustrated.•The influencing factors toward magnetocaloric effect of the molecular magnetorefrigerants are detail discussed. Zero-dimensional cluster complexes and coordination polymers for magnetic refrigeration have attracted great interest in the last decade. In-situ synthesis is a widely-used method to assemble various molecular magnetorefrigerant materials derived from different types of ligands. This review focuses mainly on the synthesis, structure and magnetochemistry of molecular magnetorefrigerant materials via in-situ synthesis, with an emphasis on in-situ generation of ligands, metal ions and templates. The first section gives a brief discussion on molecular magnetorefrigerants and some important principles obtained from magneto–structural correlation. The in-situ synthetic strategy will also be referred to and elucidated in this part. The next three sections give overviews of the main results obtained by our group and other groups in recent years, which are, in-situ generated ligands, metal ions and templates in the synthesis of molecular magnetorefrigerant materials. Finally, the conclusions and perspectives of molecular magnetorefrigerant materials will be presented. Some of the trends could provide new insights for the further development of this promising area.